Quarantine host range of Bikasha collaris, a potential biological control agent of Chinese tallowtree (Triadica sebifera) in North America. Issue 2 (28th April 2017) - Wheeler, Gregory S.; Steininger, M. Sedonia; Wright, Susan
Abstract: Chinese tallowtree, Triadica sebifera (L.) Small (Euphorbiaceae), is one of the worst invasive weeds of the southeastern USA impacting coastal wetlands, forests, and natural areas. Traditional mechanical and chemical controls have been unable to limit the spread, and this invasive species continues to expand its range. A proposed biological control candidate, the flea beetle Bikasha collaris (Baly) (Coleoptera: Chrysomelidae), shows high specificity for the target weed Chinese tallowtree. Results from a series of no‐choice and choice feeding tests of B. collaris adults and larvae indicated that this flea beetle was highly specific to Chinese tallowtree. The larvae of B. collaris feed by tunneling in the roots, whereas the adults feed on the leaves of Chinese tallowtree. A total of 77 plant taxa, primarily from members of the tallow plant family Euphorbiaceae, were tested in numerous test designs. Larval no‐choice tests indicated that larvae completed development only on two of the non‐target taxa. Of 80 B. collaris larvae fed roots of Hippomane mancinella L. and 50 larvae fed roots of Ricinus communis L., two and three larvae completed development, respectively. The emerging adults of these five larvae died within 3 days without reproducing. Larval choice tests also indicated little use of these non‐target taxa. Adult no‐choice tests indicated little leaf damage by B. collaris on the non‐targets except for Ditrysinia fruticosa (Bartram) Govaerts & Frodin and Gymnanthes lucida Sw. When given a choice, however, B. collaris adults consumed much less of the non‐targets D. fruticosa (7.4%) and G. lucida (6.1%) compared with the control leaves. Finally, no‐choice oviposition tests indicated that no eggs were produced when adults were fed all non‐target taxa, except those fed G. lucida . These B. collaris adults fed G. lucida leaves produced an average of 4.6 eggs compared with 115.0 eggs per female when fed Chinese tallowtree. The eggs produced from adults fed G. lucida were either inviable or the emerging larvae died within 1 day. These results indicate that the flea beetle B. collaris was unable to complete its life cycle on any of the non‐target taxa tested. If approved for field release, B. collaris will be the first biological control agent deployed against Chinese tallowtree in the USA. This flea beetle may play an important role in suppressing Chinese tallowtree and contribute to the integrated control of this invasive weed.